Compounds from Caesalpinia sappan with anti-inflammatory properties in macrophages and chondrocytes. Issue 3 (8th March 2016) - Mueller, Monika; Weinmann, Daniela; Toegel, Stefan; Holzer, Wolfgang; Unger, Frank M.; Viernstein, Helmut
Abstract : The heartwood of Caesalpinia sappan is a traditional ingredient of food and beverages in South East Asia and has been used in traditional medicine as an analgesic and anti-inflammatory drug or to promote blood circulation. Abstract : The heartwood of Caesalpinia sappan is a traditional ingredient of food and beverages in South East Asia and has been used in traditional medicine as an analgesic and anti-inflammatory drug or to promote blood circulation. Scientific studies have confirmed different bioactivities associated with its use. Here, five fractions were isolated from the ethanolic extract of C. sappan heartwood, including episappanol (1), protosappanin C (2), brazilin (3), (iso-)protosappanin B (4) and sappanol (5) using high-performance liquid chromatography (HPLC). All compounds were tested for their anti-inflammatory effects in two different cell lines. Cytokine concentrations in the cell supernatant were determined using enzyme-linked immunosorbent assay (ELISA), and mRNA levels were measured using reverse-transcription quantitative polymerase chain reaction (RT-qPCR). In lipopolysaccharide-stimulated macrophages, all compounds significantly inhibited the secretion of the pro-inflammatory cytokines interleukin (IL-6) and tumor necrosis factor-alpha (TNF-α). Sappanol (5) increased the secretion of the anti-inflammatory IL-10. In IL-1β-stimulated chondrocytes, all fractions reduced the mRNA expression and the secretion of the pro-inflammatory cytokines IL-6 and TNF-α. The highest anti-inflammatory effect was found for brazilin (3) in both cell lines. Of note, this is the first study which shows the anti-inflammatory effect of sappanol and episappanol. This study provides evidence for the efficacy of the traditional use of C. sappan as an anti-inflammatory remedy. Given the high prevalence of inflammation-related pathologies including arthritis, and the urgent need to clinically intervene with these diseases, the anti-inflammatory activity of diverse compounds from C. sappan may be of interest for the development of complementary and alternative treatment strategies.